Розробка функціональних схем та алгоритмів системи прийняття рішень при плануванні виконання замовлень листопрокатного виробництва - Косилов, С. О. (НТУ "ХПІ", 2014)
Розробляється система підтримки прийняття рішень при розв'язанні задачі оптимального планування для класу технологічних об'єктів конвеєрного типу з технологічною паузою перед обробкою на агрегатах і обмеженнями по часу виконання замовлень. На прикладі листопрокатного виробництва представлено результат такої розробки у вигляді структури та алгоритму роботи системи оптимального планування виконання замовлень. Пропонується метод урахування обмежень по часу при розв'язанні задачі оптимального планування.

There have been developed decision support system in solving the problem of optimal scheduling for class technological objects сonveyer type with technological pause before processing on units and limited by order turnaround time. The result of this development has been presented as a structure and algorithm of the system optimal planning of orders for sheet rolling production. In addition, the method of accounting for time constraints in solving the problem of optimal planning has been proposed. The system is implemented in the form of automatic workplace for a person who makes decisions and allows multivariate estimates of the production program. There have been made conclusions of the advantages of the developed approach to planning and increase production efficiency in its use.
Development of functional schemes and algorithms for decision-making system in the planning of orders sheet rolling production
Keywords: оптимальне планування; математичні моделі; система підтримки прийняття рішень; критерій оптимізації; час запізнення; optimal planning; mathematical models; decision support system; optimization criteria; objective function; duration of the delay